Women's self-care behavior and its relationship with social capital in Yazd, Iran - Hamideh Shiri-Mohammadabad; Seyed Alireza Afshani (BMC, 2021)
Abstract Background Research on factors affecting self-care is scarce. The social factors, in particular, have not been yet investigated in Iran. Therefore, the present study aimed to investigate the relationship between self-care and social capital among women. Methods The participants were 737 women who were living in the marginal, middle and upper areas in the city of Yazd, Iran. Data were collected using a researcher-made self-care questionnaire and Harper's (Off Natl Stat 11:2019, 2019) Social Capital Scale. The data were analyzed using structural equation modeling by SPSS and Amos v24. Results The results showed that the social capital had significant positive effects on the general self-care behavior of the participants (β = 0.56, p < 0.001). It also had significant positive effects on the self-care behavior of women living in the marginal (β = 0.58), middle (β = 0.49) and upper (β = 0.62) parts of the city (p < 0.001). Besides, the women living in the marginal parts had relatively lower levels of self-care compared to those living in the middle and upper parts of the city. The examination of the fit indices indicated that the model has a good fit (CMIN/DF = 2.087, NFI = 0.921, RMSEA = 0.027, CFI = 0.956, TLI = 0.940, GFI = 0.956, IFI = 0.957). Conclusion The findings of this study demonstrated that social capital has significant positive effects on the general self-care behavior of women. Therefore, improving their self-care can be achieved through promoting their social capital.